Criminal Justice Drug Abuse Treatment Studies (CJ-DATS): National Criminal Justice Treatment Program (NCJTP) Survey in the United States, 2002-2008 - Taxman, Faye S. ([Verlag nicht ermittelbar], 2010)
The National Criminal Justice Treatment Practices (NCJTP) Survey provides a comprehensive inquiry into the nature of programs and services provided to adult and juvenile offenders involved in the justice system in the United States. Participants included key criminal justice administrators, operations managers, and staff. This survey was conducted in all 50 states and the District of Columbia. The survey involved a myriad of state, regional, and local organizations employing a mix of their own staff and contracted personnel, and services that might involve multiple levels of government. It was a self-administrated, paper-and-pencil questionnaire. The methodology included a multilevel approach that captured the perspective of executives, front-line administrators, and line staff about current practices in a range of institutional and community correctional settings for adults and juveniles. The goals for this survey were: to describe current drug treatment practices, policies, and delivery systems for offenders on probation or parole supervision, and in jails, prisons, and youth institutions; to examine agency structures, resources, and other organizational factors that may affect service delivery, including mission, leadership, climate, culture, and beliefs about rehabilitation versus punishment; and to assess coordination and integration across criminal justice agencies and between corrections and treatment systems. Items in the survey included: respondent characteristics, organizational characteristics, correctional programs characteristics (e.g., size, nature, etc.), substance abuse treatment programs characteristics, social networks/agencies collaboration, integration of services with other agencies, attitudes toward punishment and rehabilitation (personal values), organizational needs assessment, organizational culture and climate for treatment, cynicism toward change, organizational commitment to treatment, and perspectives on intradepartmental coordination.